The implementing issues of sustainable marketing within Chinese state-owned organisations: A case study of petroleum industry in China - ZHAO, TENG (2014)
In the past few years, the environment pollution in China is getting increasingly serious. In some large cities such as Beijing and Shanghai, the individuals even cannot breathe fresh air. In such situation, due to the social public pressures, Chinese government has started to establish some regulations to guide organisations to accept the sustainable value. In this situation, the role of sustainable marketing is also getting increasingly significant.